2010
DOI: 10.3354/ame01385
|View full text |Cite
|
Sign up to set email alerts
|

Fungi in lake ecosystems

Abstract: This review highlights the presence and ecological roles of fungi in lakes, and aims to stimulate research in aquatic mycology. In the study of lentic systems, this field is an almost completely neglected topic and, if considered at all, has often been restricted to specific groups of fungi, such as yeasts, filamentous fungi (e.g. aquatic hyphomycetes), or phycomycetes (an obsolete taxonomic category that included various fungal and fungal-like organisms). We document that aquatic fungi are common in various l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
170
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(180 citation statements)
references
References 289 publications
0
170
0
4
Order By: Relevance
“…Active fungal communities within deep sub-seafloor sediments also show similar positive links to changes in the availability of organic material (Orsi et al, 2013a), and the expression of metabolic pathways involved in the cycling of a variety of organic substrates (Orsi et al, 2013b). The utilisation of particulate organic matter by benthic and pelagic marine fungi is analogous to the well-established functional roles of fungi in freshwater ecosystems, such as lakes (Wurzbacher et al, 2010).…”
Section: Discussionmentioning
confidence: 88%
“…Active fungal communities within deep sub-seafloor sediments also show similar positive links to changes in the availability of organic material (Orsi et al, 2013a), and the expression of metabolic pathways involved in the cycling of a variety of organic substrates (Orsi et al, 2013b). The utilisation of particulate organic matter by benthic and pelagic marine fungi is analogous to the well-established functional roles of fungi in freshwater ecosystems, such as lakes (Wurzbacher et al, 2010).…”
Section: Discussionmentioning
confidence: 88%
“…In recent years, Poyang Lake has suffered severely from water pollution, lake dredging, and water level fluctuations due to human activities and climate change (Lake et al 2000;Fang et al 2006). These changes might have influenced microbial communities in the sediments which, in turn, may further affect lake GHG emissions (Quayle et al 2002;Davidson & Janssens 2006;Hart 2006;Wurzbacher et al 2010;Cantarel et al 2012). Therefore, it is necessary to explore the effects of microbial biomass on GHG emissions in Poyang Lake, which can provide a firm basis for understanding GHG production and emissions from a microbial point of view.…”
Section: ¡1mentioning
confidence: 99%
“…The static littoral zone, especially the surfaces of leaf litters and sediments, is known as hot spots for fungi that participate in degrading particulate organic matters. 26,27) Niemi et al 74) reported mesophilic fungi and Actinomycetes as common species in Finnish rivers and lakes, with their occurrence being related to runoff from soil. Several degradative enzymes, including phenol oxidases, contribute to the fungal decomposition of litters, and the products are utilized by co-existing bacteria as organic nutrients for their growth.…”
Section: Microbes In Surface Watermentioning
confidence: 99%
“…3,8,18) Bacteria are more diversely populated, with their activity depending on the habitat, 25) while fungi tend to grow on a substratum, such as detritus, rather than in water. 26,27) Bacteria metabolize pesticides via various enzymatic reactions, 28) and extra-cellular enzymes such as laccases, 29) may participate in their fungal degradation. In addition to an active uptake by microbes, pesticides are adsorbed onto surfaces of microbes and biofilm, a gel-type complex mixture of microbial cells, detritus, and extra-cellular polymeric substances (EPS).…”
Section: Processes Controlling Pesticide Behaviormentioning
confidence: 99%